Atmospheric pollution in Ulaanbaatar: Persistence and long-run trends - Ariundelger Ariunsaikhan; Chultem Batbold; Sonomdagva Chonokhuu; Luis Alberiko Gil-Alana (PLoS ONE, 2025)
This paper investigates the presence of long-run trends and persistence in various pollutants in the city of Ulaanbaatar, Mongolia using fractional integration. Using daily data from January 1st, 2022 until May 31st, 2024 we investigate the statistical properties of four pollutants, namely, NO2, SO2, PM10, and PM2.5. The results indicate the presence of significant negative time trends in the cases of SO2 and PM2.5 and evidence of long memory and mean reverting patterns in all four pollutants. Policy implications of the results obtained are reported at the end of the paper.